Motivasi dan Bimbingan Orangtua terhadap Kelancaran Anak dalam Membaca Al-Quran - Lestari, Eha Anna; Prananosa, Ahmad Gawdy; Adisel, Adisel; Wahyuni, Hairun Nisa’ (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to find out what forms of motivation and guidance are given by parents to children's fluency in reading the Koran and also to find out how the results of parental motivation and guidance on children's fluency in reading the Koran. This study uses a qualitative approach. This research was carried out at TPQ Al Jihan Rt 04 Rw 03, Rawa Makmur Permai sub-district, Bengkulu City. The research subjects consisted of Koran teachers, parents and TPQ students. Data collection techniques include; observation, interviews and documentation, data analysis techniques using data reduction, data display, and verification / drawing conclusions. The results of the study, as for the forms of motivation and guidance provided by parents are parents asking the obstacles faced by children in learning the Koran, giving understanding to children about the importance of studying the Koran as Islamic character formation, giving gifts/punishments to children, facilitating children in learning, and provide encouragement and motivation, while the form of guidance given by parents is attention when children study, guiding children when reading the Koran, scheduling Koran learning activities at home. In conclusion, from the forms of motivation and guidance that have been given by parents, the results are very good for children who are also guided by their parents at home, not only relying on studying at TPQ, if the motivation and guidance are good the results obtained are also good, and vice versa. Keywords: Motivation, Guidance, Parents, Fluency in reading the Koran, TPQ